Low Back Pain Versus Back-Related Leg Pain: How Do Patient Expectations and Outcomes of Lumbar Spine Surgery Compare?. Issue 1 (February 2022) - Brusalis, Christopher M.; Duculan, Roland; Cammisa, Frank P.; Sama, Andrew A.; Hughes, Alexander P.; Mancuso, Carol A.; Girardi, Federico P.
Background : An increasing number of lumbar spine conditions are treated surgically. Such intervention, however, is commonly thought to be more effective in addressing leg pain than low back pain. Patient expectations may also contribute to self-reported surgical outcomes. Questions/Purposes : We sought to compare the expectations of patients in 2 groups undergoing lumbar spine surgery: those with predominantly low back pain and those with predominantly leg pain. We also sought to evaluate how these expectations were fulfilled for each group. Methods : We carried out a retrospective analysis of prospectively collected data from a prior study in which patients scheduled for lumbar spine surgery at a single institution completed validated surveys preoperatively and at 2 years postoperatively, including a 20-item survey on expectations for lumbar spine surgery. The patients were enrolled in the study between February 2010 and August 2012, and were divided into 2 cohorts: a "Back > Leg" group that consisted of patients with back pain that was isolated or greater than leg pain, and a "Leg ≥ Back" group that consisted of patients with leg pain that equaled or exceeded back pain. The primary analysis compared composite expectation scores (range, 0–100) between groups. Results : A total of 366 patients were deemed eligible for the study; of these, 162 patients were allocated to the Back > Leg group and 204 patients were allocated to the Leg ≥ Back group. Patients in the Leg ≥ Back group had a greater mean preoperative expectation score compared with those in the Back > Leg group. Multivariate analysis demonstrated that higher preoperative expectations were associated with leg pain symptoms after controlling for disease diagnosis. Both groups reported similar proportions of fulfilled expectations. Conclusion : Patients with predominantly leg pain hold greater preoperative expectations for lumbar spine surgery than do patients with predominantly back pain. That these patient groups reported similar fulfillment of their expectations at 2 years postoperatively illustrates the greater clinical outcomes achieved among patients who presented with predominantly leg pain.